KETAHANAN PANGAN RUMAH TANGGA TANI DI DAERAH ALIRAN SUNGAI (DAS) GALEH KABUPATEN SEMARANG - Ahmad Rifai; Suprapti Supardi; Dewi Hastuti (MEDIAGRO, 2012)
The study, entitled "Food security of farm households in the Galeh Watershed Semarang Regency" has an objective to determine the composition of farm household characteristics, income levels and food security of farm households annually. This research used survey method. Research area was determined using purposive sampling method which is in Semarang Regency Village Genting, Rejosari, Brongkol, Kemambang, Ngrapah, and Rowoboni. Respondents are determined by random sampling of 120 households in six villages. Survey results showed that the average age of head family in farm households of Galeh Watershed age is 44.90 years old, which is categorized as productive age group.  Farmers in these villages have an average size of rice fields about 0.26 ha  while average size of garden and land tenure owned are 0.210 and 0.215 ha. Goats are the main livestock in the Galeh Watershed, every family in these villages has more or less 2 goats. Average of income levels of farm household in this watershed is Rp 22,533,792.00. Dominant commodities producing in these villages are paddy, coffee, chili and cauliflower. Rice farming in Rowoboni village has a good performance compared to other village with R/C ratio 2.94. Meanwhile, in Genting village, coffe and red papper farming have given higher performance than other village with R/C ratio 2.03 and 1.64 consecutively.  R/C ratio of White pepper in Rejosari village is 1.61, and cauliflower is in Kemambang Village, with its R/C ratio 1.48. Share of household expenditure is dominated by food expenditure, with average 52.63% of total expenditure in one year. Non-food expenditure of farm households in the Galeh watershed is dominated by children's education costs, which reached an average of 10.71% a year. Purchasing power of farm households in the watershed Galeh is 116.30%, which means that all farm households in the Galeh watershed are able to meet all their needs both food and non food and still have remaining 16.3%. The criteria of household food security levels in Galeh Watershed Semarang Regency considered surplus which reached 1.27. It means that they can produce their own rice around 1,857.15 kg/year and household rice consumption equivalent to 1,456.80 kg/year. Keyword : food security, outcome, income, household.